Film collection: PRECIOUS Preciosa (Journal of Parents and Teachers, 2013)
In this section of the magazine, the film Precious Preciosa is proposed for working with the students of the higher grades of Secondary Education topics and values like health education, family education, marginalization and social education, respect, tolerance, self-esteem or communication. It contains an index card of the film, activities to do before watching the film and reflection activities analyzing scenes after watching it.
Keywords: Values; Emotional Education; Family Education; Social Education; education and centerfold